The evaluation of an integrated network approach of preventive care for children with overweight and obesity; study protocol for an implementation and effectiveness study - Sanne de Laat; Iris de Vos; Monique Jacobs; Edgar van Mil; Ien van de Goor (BMC, 2019)
Abstract Background Children with overweight often do not receive appropriate integrated care. An innovative integrated network approach of preventive care for overweight children aged 4-12 years old has been developed and implemented in four neighbourhoods of 's-Hertogenbosch, The Netherlands. This new approach focusses on self-management of the family and is based on the principles of stepped and matched care. Youth health care (YHC) nurses support the families in their new role as central care providers. The aim of this study is to evaluate the implementation and effectiveness of this network approach. Methods The implementation of the new approach (reach, functioning of the central care provider, network functioning and patient satisfaction) is assessed by interviews and checklists with professionals and parents of 4-12 year old overweight or obese children. To evaluate effectiveness, we aim to compare 120 overweight or obese children in 's-Hertogenbosch with 60 overweight or obese children outside 's-Hertogenbosch during one year of YHC involvement. Quality of life, psychosocial problems of the child and parental empowerment are the main outcomes of the effectiveness study. Outcomes are measured with digital questionnaires at inclusion, at three months and one year after inclusion. BMI measurements and referrals are distracted from medical files. Discussion Integrated care for overweight and obese children is high on the agenda of many municipalities in The Netherlands. The new approach is expected to have beneficial effects for overweight children, their parents and professionals. With the results of this study, we can optimize the support for overweight and obese children and their parents. The first results are expected to be available in 2019. Trial registration This study is registered in the Dutch Trial Register on 10 November 2017 (NTR number NTR6813). https://www.trialregister.nl/trial/6596 Word count: 281 (max 350).